Tinjauan Hukum Kesesuaian Pelaksanaan Yayasan Dengan Undang-Undang Yayasan - Ilma, Natasya Nurul (Faculty of Law Universitas Islam Indonesia, 2024)
The implementation of foundations in Indonesia must comply with applicable laws. The problems formulated in this research are: how the implementation of foundations in practice must comply with the Foundation Law, and what is the role of notaries in the creation of deeds related to foundations. This research employs a normative juridical methodology, utilizing both statutory and case approaches. The data is analyzed using a qualitative descriptive method, grounded in the theories of legal validity, legal certainty, and legal protection. The findings of this study indicate that, first, the practical implementation of foundations remains inconsistent with and, in some cases, contrary to the mandates of the Law on Foundations. This is evidenced by the existence of instruments such as powers of attorney for branch operations, deeds reaffirming resolutions of the foundation's board of supervisors, and interventions by parties external to the foundation's statutory organs. Second, with regard to the role of notaries in the preparation of deeds relating to foundations, notaries are legally obligated to provide legal counseling to parties appearing before them, as stipulated in Article 15 paragraph (2) letter e and Article 16 paragraph (1) letter a of the Indonesian Notary Law (UUJN). This obligation ensures the protection of the parties' interests in legal acts formalized in notarial deeds. Furthermore, notaries are required to fulfill all formal aspects of deed preparation to ensure material accuracy and adherence to prevailing legal norms.